Monopoly and Competition in Europe and America - Scitovsky, Tibor (Quarterly Journal of Economics, 1955)
Journal Article Monopoly and Competition in Europe and America Get access Tibor Scitovsky Tibor Scitovsky Stanford University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 69, Issue 4, November 1955, Pages 607–618, https://doi.org/10.2307/1881997 Published: 01 November 1955